2015
DOI: 10.1039/c5gc01195g
|View full text |Cite
|
Sign up to set email alerts
|

Application of cyanobacteria for chiral phosphonate synthesis

Abstract: This is the first report on morphologically different strains of cyanobacteria: Arthrospira maxima, Nostoc cf-muscorum and Nodularia sphaerocarpa used for enantioselective bioreduction of selected, structurally different diethyl esters of oxophosphonic acids. The efficiency of the asymmetric hydrogen transfer was strongly dependent on the chemical structure of the substrates. Arthrospira maxima was active only toward diethyl (S)-2-oxopropylphosphonate (20% of yield, 99% of ee), whereas the application of Nosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
6

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 37 publications
5
37
0
6
Order By: Relevance
“…Using wildtype cells without the recombinant BVMO, we did not observe any measurable oxidation of any of the ketones. Ketoreduction by endogenous alcohol dehydrogenases [12], and the selective reduction of cinnamyl aldehyde in Synechocystis have been reported before [11]. Indeed, we also found that wildtype Synechocystis cells without the chmo gene catalysed the reduction in 1a and 1c-f to the corresponding alcohols.…”
Section: Substrate Spectrum and Side-reactionssupporting
confidence: 83%
See 3 more Smart Citations
“…Using wildtype cells without the recombinant BVMO, we did not observe any measurable oxidation of any of the ketones. Ketoreduction by endogenous alcohol dehydrogenases [12], and the selective reduction of cinnamyl aldehyde in Synechocystis have been reported before [11]. Indeed, we also found that wildtype Synechocystis cells without the chmo gene catalysed the reduction in 1a and 1c-f to the corresponding alcohols.…”
Section: Substrate Spectrum and Side-reactionssupporting
confidence: 83%
“…In biotransformation reactions with a substrate concentration of 5 mM, the methyl-substituted ketones 1c-e were converted with a specific activity between 2 to 5 U/gCDW (Tables 1 and 2). This activity is a result of the Baeyer-Villiger oxidation and the competing Ketoreduction by endogenous alcohol dehydrogenases [12], and the selective reduction of cinnamyl aldehyde in Synechocystis have been reported before [11]. Indeed, we also found that wildtype Synechocystis cells without the chmo gene catalysed the reduction in 1a and 1c-f to the corresponding alcohols.…”
Section: Substrate Spectrum and Side-reactionssupporting
confidence: 80%
See 2 more Smart Citations
“…Enantioselectivity as well as cell viability remained almost at the same level (Górak and Żymańczyk-Duda 2015). Thus, current efforts involve an increase in both values and were also focused on creating the economic system that allows reuse of biocatalyst.…”
Section: Discussionmentioning
confidence: 86%